Surface coating of UF membranes to improve antifouling properties: A comparison study between cellulose nanocrystals (CNCs) and cellulose nanofibrils (CNFs). (February 2019) - Bai, Langming; Liu, Yatao; Ding, An; Ren, Nanqi; Li, Guibai; Liang, Heng
Abstract: The inherent properties of hydrophilicity and environmental preferability of cellulose nanocrystals (CNCs) and cellulose nanofibers (CNFs) make them great candidates for application in water-treatment membranes. In this study, the antifouling properties of CNCs and CNFs, modified ultrafiltration (UF) membranes, were directly compared. A facile modification method was conducted by coating CNCs and CNFs on the surface of polyethersulfone (PES) membranes to prepare CNC-coating membranes and the CNF-coating membranes. Membrane surface morphology was characterized by atomic force microscopy (AFM), and the results showed that the CNF-coating membranes exhibited greater surface roughness than the CNC-coating membranes. Pure water flux measurements demonstrated that the flux of the CNC-coating membranes was slightly lower than that of the CNF-coating membranes. Antifouling properties were evaluated and compared for the two types of membranes by filtration of NOM foulant models, humic acid (HA) and bovine serum albumin (BSA). The results showed that the antifouling properties of the modified membranes were enhanced through the coating of either CNCs or CNFs to a control PES membrane. The CNC-coating membranes outperformed the CNF-coating membranes in alleviating both reversible fouling and irreversible fouling caused by HA and BSA. In addition, the antifouling performance of the coating membranes was enhanced with increased coating content. Graphical abstract: Highlights: CNCs and CNFs were coated on the surface of UF membranes. Surface roughness of the CNF-coating-M was greater than that of the CNC-coating-M. The pure water flux of the CNC-coating-M was lower than that of the CNF-coating-M. The CNC-coating-M outperformed the CNF-coating-M in membrane fouling control. Both reversible and irreversible fouling can be decreased by the CNC-coating layer.